ANALYSIS OF THE INTRA-ANNUAL FLOW DISTRIBUTION OF THE SYRDARYA RIVER UNDER DIFFERENT HYDROLOGICAL CONDITIONS (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The study examines the characteristics of the intra-annual distribution of the Syrdarya River runoff under conditions of water management regime transformation. Based on the analysis of hydrological observations from the section between the village of Kal and the downstream of the Chardara Reservoir, changes in the seasonal runoff structure during wet, average, and dry years have been identified. Following the transition of the Naryn basin reservoirs to an energy-oriented regime since 1991, peak discharges have shifted to the autumn-winter period, accompanied by a reduction in summer runoff, which has complicated irrigation water supply. A comparative assessment of seasonal runoff distribution was carried out for the periods 1980–1990 and 2011–2021. The necessity of constructing regulatory reservoirs in Uzbekistan and Kazakhstan to stabilize water availability has been substantiated.